Post-buckling behavior of carbon fiber epoxy composite plates - Erdem, Serkan; Kaman, Mete Onur; Gur, Mustafa (Korean Soc Mechanical Engineers, 2019)
In this study, the pre-buckling and post-buckling behaviors of layered composite plates which were made of woven carbon fiber fabric with a circular hole in the middle were investigated experimentally and numerically. Firstly, load-displacement graphs of composite plates with different hole diameters were experimentally obtained under compressive load. Then the numerical load-displacement graphs of the plates were found with the ANSYS package program which used the finite element method. As a result, after linear buckling experimental and numerical results were found to be compatible with each other. In addition, damage behavior of plates after buckling with the aid of Tsai-Wu damage criterion was obtained similar to experimental results. The increase in hole diameter did not change the load-displacement behavior characteristics of the plates after buckling. However, it has reduced maximum damage load and maximum failure displacement. The stress at the perimeter of the hole increased significantly with the increase of the vertical displacement with immediately after the buckling but later was not significantly affected by this increase.
Keywords: Laminated composite plates; Post-buckling; Finite element method; Compression test